2019
DOI: 10.1038/s41526-019-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of low-dose, high-energy radiation on bone in partial- and/or full-weightbearing mice

Abstract: Astronauts traveling beyond low Earth orbit will be exposed to galactic cosmic radiation (GCR); understanding how high energy ionizing radiation modifies the bone response to mechanical unloading is important to assuring crew health. To investigate this, we exposed 4-mo-old female Balb/cBYJ mice to an acute space-relevant dose of 0.5 Gy 56 Fe or sham ( n = ~8/group); 4 days later, half of the mice were also subjected to a ground-based analog for 1/6 g (partial weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, the effect of radiation on bones is still under investigation. In fact, in a study on skeletally mature mice (16 weeks of age) exposed to 0.5 Gy of 56 Fe, some positive effects were documented [ 82 ]. Aside from IR, MG can be harmful to the skeletal system for many reasons (e.g., mechanical loading, altered calcium homeostasis, decreased hematopoiesis, and altered metabolism) [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of radiation on bones is still under investigation. In fact, in a study on skeletally mature mice (16 weeks of age) exposed to 0.5 Gy of 56 Fe, some positive effects were documented [ 82 ]. Aside from IR, MG can be harmful to the skeletal system for many reasons (e.g., mechanical loading, altered calcium homeostasis, decreased hematopoiesis, and altered metabolism) [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research already identified synchronous effects of HLU and high doses of radiation, with the majority supporting the hypothesis that high-dose irradiation exacerbates the skeletal consequences of mechanical unloading [19][20][21][22]. For example, cancellous bone losses were driven by similar osteoclastic bone resorption in HLU and gamma irradiation, in 4-month-old C57BL/6 mice, with an additive effect of these two interventions [20].…”
Section: Introductionmentioning
confidence: 60%
“…Furthermore, proton radiation and high atomic number and energy radiation (HZE) also produced additive bone losses in the C57BL/6 mouse strain [21]. However, one must consider the interesting finding of the protective effects of high-linear energy radiation exposure with 0.5 Gy 56 Fe, prior to mechanical unloading, in the weight-bearing bones of the legs of 4-month-old female Balb/cBYJ mice [22]. Nevertheless, despite the increasing body of research combining HLU with relatively high doses of radiation, combined low-dose radiation and HLU research remain sparse.…”
Section: Introductionmentioning
confidence: 99%